The Impact of Marriage Dispensation on the Economic Welfare of Sharia Perspectical Families (Analysis Study in Poncol Village, Magetan Regency) - Barra Hannan Al Harist; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
.  Marriage dispensation cases often occur among the community, especially in rural areas. The purpose of this study is to find out more about how the impact of marriage dispensation will have on the economic welfare of families in Poncol Village, Magetan Regency in terms of sharia perspectives. The type of research is a literature review with descriptive qualitative methods and its implementation using the Preferred Reporting Project for Systematic Evaluation and Meta-Analysis. The results showed that Sharia has explained about the guarantee from Allah regarding the opening of the door of fortune for someone who gets married. Regarding economic welfare, there is already a guarantee from God. Early marriage is allowed with the aim of benefit.